The Path to Obergefell: Saying “I do” to New Judicial Federalism? - Christine L. Nemacheck (Washington University Journal of Law & Policy, 2017)
This Article analyses the significant role of state laws had helping shape the Supreme Court’s landmark decision for same-sex marriage in Obergefell v. Hodges. Nemacheck connects this success to a judicial federalism proposed by Justice Brennan in 1977, in which Brennan identified the process for protecting individual rights by litigating cases at the state court level. The Article identifies strategies from same-sex marriage advocates of first attaining protections at the state level, then move litigation toward to the Supreme Court once a significant numbers of states had approved. The author cites this state-level strategy as the necessary groundwork for the Obergefell decision, which occurred after marriage equality had already been approved in 36 states and Washington D.C.
Keywords: Roberts Court; Obergefell; Supreme Court; same-sex marriage; marriage equality; federalism